02.05. Elektrik & Elektronik Mühendisliği - (:unkn) unknown (My University, 2025)
Öğretim, araştırma ve sosyal etki boyutlarında lider bir Elektrik-Elektronik Mühendisliği Bölümü olmak amaçlanmaktadır.

It is aimed to be a leading Electrical and Electronics Engineering Department in teaching, research and social impact.